Electron-paramagnetic-resonance spectroscopy studies of iron-sulphur centres of submitochondrial particles from iron- and sulphur-deficient. Candida utilis. - Gray, T A (1975)
1. Measurements were made at 12 degrees K of the electron-paramagnetic-resonance (e.p.r.) spectra of submitochondrial particles from Candida utilis cells grown under conditions that alter the amount of the mitochondrial NADH dehydrogenase (EC 1.6.99.3). 2. Iron-limited growth decreases the extent of iron-sulphur e.p.r. signals to undetectable values that are less than 1 percent of those normally found with glycerol-limited growth. 3. Small but significant signals attributable to the NADH dehydrogenase were detected in submitochondrial particles from sulphate-limited cells. 4. Measurements made on submitochondrial particles prepared from these and other phenotypically modified cells lead us to conclude that the presence of low-temperature e.p.r.-detectable iron-sulphur centres attributable to the NADH dehydrogenase are necessary but not sufficient for the coupling of ATP synthesis to the NADH dehydrogenase reaction in the mitochondrial membrane of C. utilis. 6. The amplitude of the g=2.01 signal observed in non-reduced submitochondrial particles is approximately tenfold diminished by iron limitation but not significantly altered by sulphate limitation.